Work Posture Analysis to Identify Musculoskeletal Disorders (MSDs) Risk Among Production Workers at PT Gramasurya Yogyakarta - Ni Kadek Pujiani Dewi; Andhika Rama Biyanto (JUMANTARA: Jurnal Manajemen dan Teknologi Rekayasa, 2026)
This study addresses musculoskeletal disorder (MSDs) risks among manual production workers in the printing industry by integrating subjective complaint mapping, digital body-angle measurement, and ergonomic risk scoring. The objective was to quantify changes in musculoskeletal complaints and identify priority ergonomic interventions at the cutting, bending, and packaging workstations of PT Gramasurya Yogyakarta. A descriptive quantitative design was applied to three purposively selected workers representing the three critical workstations. Data were collected through direct observation, brief interviews, Nordic Body Map assessment before and after work, posture documentation, AutoCAD-based angle measurement, and REBA/RULA scoring. The NBM score increased from 31 to 40 in cutting, 32 to 54 in bending, and 39 to 76 in packaging. Postural analysis showed REBA 7 for cutting, RULA 4 for bending, and REBA 9 for packaging, with packaging presenting the highest risk due to 90° trunk flexion, 80° upper-arm angle, and 41° wrist deviation. The study contributes an integrated ergonomic evaluation pathway linking worker complaints, digital angle measurement, risk score, and intervention priority. Recommended improvements include a packaging table, hand stacker for material handling, and height-adjusted seating or worktable arrangements, with post-intervention reassessment required to validate risk reduction.